Application of the PISA design model to monopiles embedded in layered soils - Burd, H; Abadie, C; Byrne, B; Houlsby, G; Martin, C; McAdam, R; Jardine, RJ; Pedro, AMG; Potts, DM; Taborda, DMG; Zdravkovic, L; Pacheco Andrade, M (Thomas Telford, 2020)
The PISA design model is a procedure for the analysis of monopile foundations for offshore wind turbine applications. This design model has been previously calibrated for homogeneous soils; this paper extends the modelling approach to the analysis of monopiles installed at sites where the soil profile is layered. The paper describes a computational study on monopiles embedded in layered soil configurations comprising selected combinations of soft and stiff clay and sand at a range of relative densities. The study comprises (a) analyses of monopile behaviour using detailed three-dimensional (3D) finite-element analysis, and (b) calculations employing the PISA design model. Results from the 3D analyses are used to explore the various influences that soil layering has on the performance of the monopile. The fidelity of the PISA design model is assessed by comparisons with data obtained from equivalent 3D finite-element analyses, demonstrating a good agreement in most cases. This comparative study demonstrates that the PISA design model can be applied successfully to layered soil configurations, except in certain cases involving combinations of very soft clay and very dense sand.